KEPATUHAN ORANG TUA DALAM PEMBERIAN KELENGKAPAN IMUNISASI DASAR PADA BAYI 4—11 BULAN - Niken Febriastuti; Yuni Arief; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2014)
Introduction: The low rate of completed immunization increas babies morbidity. Analysis of parent’s adherence in giving complete basic immunization to their baby is need to be done. The purpose of this study was to parent’s adherence in giving complete basic immunization to their baby at Puskesmas Kenjeran in Surabaya. Method: In this study description analysis research method was used. The sample  of this research was 36 mothers having a baby with age 4-11 months and came to get immunizatin for their baby. The instrument of this research was modified questionnaire based on Planned Behavior Theory. Data collected analysis used multiple regression with significance value α≤0,05.Result: The result of double linier regression test is p(Sig.) = 0,000 <0,05 and coefficient determination score (R Square) is 0,837. Partial test result for attitute variable scored (p=0,016), subjective norm variable scored (p=0,013), perseption variable scored (p=0,012), and intention variable scored (p=0,042).Discussion: According to this research we can conclude that factors of parent’s adherence which are attitute, subjective norm, perception and intention partially and stimulantaneously affected parent’s adherence in giving basic immunization to their baby. Health education to parents about giving basic immunization for baby should be increased in order to prevent a variety of diseases that can be prevented by immunization.